Pengaruh Kualitas Produk, Harga dan Word of Mouth terhadap Keputusan Pembelian: Studi Pada UMKM Produk Kreatif di Desa Pedungan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the influence of product quality, price and word of mouth on creative product MSMEs in Pedungan Village. This research was conducted on Creative Product MSMEs in Pedungan Village with a total sample of 75 samples using a sampling technique using accidental sampling. The data used comes from primary data and secondary data. The test carried out is in the form of a classic assumption test. The analytical method used is multiple linear regression analysis. Next, the coefficient of determination test, t test and F test were carried out. From the results of the analysis it was found that (1) Product Quality had no effect on Purchasing Decisions; (2) Price has a significant positive effect on Purchasing Decisions; (3) Word of mouth has a significant positive effect on Purchasing Decisions; (4) Product Quality, Price and Word of mouth have a significant positive effect on Purchasing Decisions. The suggestion that the researcher wants to convey is that future researchers are expected to be able to research and examine more deeply other factors that were not examined in this research which could influence purchasing decisions.